(untitled) - Davidson, Paul J. (Singapore, 1997)
Investment In South East Asia covers much more than the law and policy relating to foreign investment in South East Asia. It provides a comprehensive, readable and practical guide to all aspects of investment.
Keywords: Đầu tư, nước ngoài,Investments, foreign; Luật và pháp luật,Law and legislation; Đông Nam Á,Southeast Asia